A comparative study investigating the use of manipulatives at the transition from primary to post-primary education. Issue 6 (17th August 2020) - O'Meara, Niamh; Johnson, Patrick; Leavy, Aisling
Abstract : The transition from primary to post-primary education is considered the most difficult of all educational transitions, with negative effects more pronounced for mathematics. One factor affecting the fluidity of transition is discontinuities in pedagogical approaches. This study investigates one pedagogical approach, the use of manipulatives, to identify if discontinuities exist in their usage between primary and post-primary mathematics education. A questionnaire was distributed to teachers teaching students in their final year of primary school and teachers teaching mathematics to first-year students in post-primary school. Results reveal disparities in teachers' responses. A significantly larger proportion of primary teachers report using manipulatives in three or more lessons per week than their post-primary colleagues. This shows a discontinuity in the educational experiences of students which contributes to ineffective transition. Reasons for the existence of this discontinuity were identified. Teachers' confidence levels and the perceived usefulness of manipulatives may account for greater use of manipulatives at primary level but this study found that these reasons stemmed from the lack of training available to post-primary mathematics teachers. A large number of primary teachers reported receiving training in the use of manipulatives but for post-primary teachers this training, consisted of ' one lecture on algitiles ', at best.